2022
DOI: 10.1021/acs.langmuir.2c01694
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Adsorptive Drug Loading on Silica Aerogels from Supercritical CO2

Abstract: This work gives an insight into the process of adsorptive drug loading in silica aerogels from supercritical CO2 (scCO2). A prevalent method for such loading entails bringing the aerogels into contact with the drug–scCO2 solution followed by slow or isothermal depressurization. Our previous work established that drug precipitates during depressurization. Consequently, the adsorptive drug loading measured by the prevalent method includes precipitation. An alternative method is presented for accurate measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Two critical aspects of drug development are determining the ideal dosage and creating effective formulations for controlled release [ 1 , 2 ]. Recently, several researchers have proposed various methods based on supercritical fluid technology, such as micronization [ 3 ]; the creation of multicomponent crystals [ 4 , 5 ]; microencapsulation [ 6 ]; impregnation [ 7 ]; adsorbing drugs onto porous carriers [ 8 ]; and co-precipitation [ 9 ] to address the issue of low dissolution rate. The dissolution rate of drugs is increased by adsorption in an amorphous state [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two critical aspects of drug development are determining the ideal dosage and creating effective formulations for controlled release [ 1 , 2 ]. Recently, several researchers have proposed various methods based on supercritical fluid technology, such as micronization [ 3 ]; the creation of multicomponent crystals [ 4 , 5 ]; microencapsulation [ 6 ]; impregnation [ 7 ]; adsorbing drugs onto porous carriers [ 8 ]; and co-precipitation [ 9 ] to address the issue of low dissolution rate. The dissolution rate of drugs is increased by adsorption in an amorphous state [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have noted that the efficiency of such drugs remains unchanged during storage [ 4 , 5 , 6 , 7 ]. Singh N. et al have shown that due to high surface area, silica aerogels (AG) are an effective carrier material for poorly water-soluble drugs [ 8 ]. The results show [ 9 ] that tetraethyl orthosilicate (TEOS) [ 10 ]-doped aerogel had significantly better morphology, structure, and characteristics than the non-TEOS aerogel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation